Development of a Holistic Curriculum for Islamic Education at the State Madrasah Ibtidaiyah (MIN) 1 Berau - Nurul Hidayah; Khozin Khozin; Abdul Haris (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to understand the holistic curriculum and analyze the development and implementation of a holistic curriculum in Islamic education at MIN 1 Berau. This study uses a qualitative approach with a case study research type and data collection techniques using observation and interviews. The research results obtained are First, a holistic curriculum is a comprehensive curriculum that seeks to balance all aspects of life to foster awareness of the relationship with the environment and God, which is the ultimate goal of life. Second, the purpose of Islamic education is to prepare students to carry out the mission given by Allah, namely as caliphs and servants of Allah, so there must be an effort to balance material and spiritual life, individual and social, knowledge and morals, which is by holistic education for balancing all the potential that exists in life. Third, implementing the Holistic Curriculum at MIN 1 Berau has not been carried out comprehensively because education only develops knowledge and has yet to develop the realm of skills and student attitudes.